Plasmodial HSP70s are functionally adapted to the malaria parasite life cycle - Przyborski, Jude M.; Diehl, Mathias; Blatch, Gregory L. (Frontiers in Molecular Biosciences, 2015)
The human malaria parasite, Plasmodium falciparum, encodes a minimal complement of six heat shock protein 70s (PfHSP70s), some of which are highly expressed and are thought to play an important role in the survival and pathology of the parasite. In addition to canonical features of molecular chaperones, these HSP70s possess properties that reflect functional adaptation to a parasitic life style, including resistance to thermal insult during fever periods and host–parasite interactions. The parasite even exports an HSP70 to the host cell where it is likely to be involved in host cell modification. This review focuses on the features of the PfHSP70s, particularly with respect to their adaptation to the malaria parasite life cycle.